2017
DOI: 10.4028/www.scientific.net/jera.31.20
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and Recrystallised Texture Evolution and the Followed Mechanical and Electrical Properties of Drawn and Annealed Copper Wires

Abstract: Copper destined for electrical cabling require a compromise of mechanical properties and electrical resistivity. The drawing process accompanied by the formation of crystalline defects, such as gaps and dislocations, which leads to the increase in hardness, and therefore to the increase in resistivity, a very important characteristic for the conductivity and the efficiency of the cable. The scope of this work is to investigate the phenomenon of deformation texture evolution while copper wire drawn destined for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The elongated grains align parallel to the drawing direction. According to Fellah [12] and Baci et al [13], when the degree of deformation increases, the drawn wire acquires a textured microstructure so-called "wire-drawing of texture" [14,15]. Zidani et al [16] have also observed this kind of texture in the cold-drawn aluminum alloy (6101).…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…The elongated grains align parallel to the drawing direction. According to Fellah [12] and Baci et al [13], when the degree of deformation increases, the drawn wire acquires a textured microstructure so-called "wire-drawing of texture" [14,15]. Zidani et al [16] have also observed this kind of texture in the cold-drawn aluminum alloy (6101).…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…stored elastic energy) in the material. This results in heterogeneity of the microstructure and the crystallographic texture within the grains [12][13].…”
Section: Evolution Of Mechanical Properties Of Wires Drawnmentioning
confidence: 99%
“…For the case of Cold drawn wires process in the open air space and at room temperature for two years, we inspect first the presence of precipitates in the microstructure and study the effect of heat treatment on the activation of this phenomenon [1]. The second objective of this work is to see the effect of natural and thermal aging on the microstructural evolution of cold-drawn aluminum wires (AGS) 6101 [2][3][4][5]. The characterization methods used in this work are optical microscopy (OM), scanning electron microscopy (SEM) and X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%